1987
DOI: 10.1002/j.1460-2075.1987.tb04866.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional termination at a fully rho-independent site in Escherichia coli is prevented by uninterrupted translation of the nascent RNA.

Abstract: We have examined the possibility that translation reading through a fully rho‐independent transcriptional terminator in Escherichia coli might prevent termination, as already established for rho‐dependent terminators. Plasmids were constructed with and without interposition of the rho‐independent coliphage T7 ‘early’ terminator between a promoter and galK. Our constructions ensured either that there was no upstream translation, or that translation (initiated at the galE ribosome binding site) stopped upstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 35 publications
3
28
0
Order By: Relevance
“…The results show that translocation abrogates transcription termination, thus confirming the central tenet of the model. Consequently, these results support the proposed role of RNA interactions in the termination mechanism, as the ability of ribosomes to disrupt RNA structures is well documented (Wright and Hayward 1987).…”
Section: Discussionsupporting
confidence: 80%
“…The results show that translocation abrogates transcription termination, thus confirming the central tenet of the model. Consequently, these results support the proposed role of RNA interactions in the termination mechanism, as the ability of ribosomes to disrupt RNA structures is well documented (Wright and Hayward 1987).…”
Section: Discussionsupporting
confidence: 80%
“…1). Results from several laboratories (2,22,27,38,39) support the proposal of Stanssens et al (33) that transcriptional polarity does not require complete arrest of translation, as is the case with the polarity caused by nonsense mutations (26). Increased spacing between the RNA polymerase and the leading ribosome would seem to satisfy the requirements for intracistronic termination to occur.…”
Section: Vol 177 1995 Notes 1897supporting
confidence: 61%
“…The vectors employed for human ␤-pol expression were designed to maximize the probability of efficient translation initiation of the ␤-pol mRNA. It has been shown that efficient translation of an mRNA can protect it from degradation (36) and prevents or greatly reduces rho-dependent and rho-independent transcription termination (37,38). Since initiation is usually the rate-limiting step in translation (39), it follows that it is appropriate to focusing on maximizing translation initiation efficiency of mRNAs targeted for overproduction in E. coli.…”
Section: Discussionmentioning
confidence: 99%